OPTIMALISASI EFISIENSI OUTPUT LISTRIK DARI SOLAR CELL PADA CUACA MENDUNG - Bisyri, Ahmad Janukhi; Sudarti, Sudarti Sudarti; Yushardi, Yushardi Yushardi (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2022)
Solar radiation has a great effect on the output of the photovoltaic system. The influence of temperature, placement position, constituent material and cooling system can affect the performance of the solar collector. This research looks at the influence of temperature, placement position, constituent materials and cooling system. From the results obtained, solar panels work better to absorb sunlight when the temperature of the solar panels drops. The position of the solar panel is always facing the sun so that it can operate optimally. With good quality solar panel materials, it can increase the work efficiency of solar panels quite drastically. From the results of the tests, we can conclude that the efficiency of the solar panels from the entire experiment increased so that they could work if the weather was bad.